The reception of penicillin in Portugal during World War II: cooperation with Brazil and the United States of America - Bell, Victoria (2015)
The discovery of penicillin in 1928 and its introduction as therapeutic agent in the 1940’s significantly altered the prognosis of infectious diseases and represented the starting point for research that led to the discovery of other antibiotics. Portugal was one of the first European countries, non-participant in the II World War, to obtain penicillin for civilian use. World production of the antibiotic was scarce and military forces and government appointed research centers absorbed the limited amount available. Good diplomatic relations between Portugal, Brazil and the United States of America (USA) were decisive in attaining penicillin for our country. In May of 1944, the Brazilian government offered Portugal 12 vials of penicillin. During the summer of 1944, as the Portuguese and American governments negotiated the use of the Lages military base in the Azores, they also discussed the terms regarding a regular supply of penicillin for Portugal. In order to import penicillin from the USA, Portugal was obliged to establish a controlling committee to oversee the allocation and distribution of the antibiotic. The Portuguese Red Cross played a major role in this event, on July 26, 1944 the humanitarian institution appointed the Junta Consultiva para a Distribuição de Penicilina em Portugal (JCDPP) to act as a controlling committee. The first allotment of 700 vials, each containing 100 000 units of penicillin, arrived at Lisbon airport on September 8, 1944. In January 1945, the US government increased the monthly allotment to 1000 vials and in March 1945 to 1500 vials. As world production of penicillin increased, controlling committees were no longer necessary. In June 1945, the Portuguese Red Cross terminated the JCDPP and the Portuguese pharmaceutical industry began to import the antibiotic. Cooperation with Brazil and the USA was vital for Portugal to attain penicillin. It enabled the antibiotic to become available to the Portuguese civilian population when its use was still restricted to the military forces. The in advanced acquisition of penicillin in Portugal that resulted from nation cooperation saved many lives to and initiated a new era in the treatment of infectious diseases.http://dx.doi.org/10.14195/1647-6336_13_9